MODEL STRUCTURE CONDUCT PERFORMANCE DALAM MENGUKUR TINGKAT EFISIENSI PASAR PADA INDUSTRI PERBANKAN SYARIAH - Kusumo, Willyanto Kartiko; Novasari, Linda Ayu Oktoriza (Jurnal Dinamika Sosial Budaya, 2018)
Efficiency is one of the performance parameters that is theoretically one of the performance that underlies the entire performance of an organization. Efficiency in the banking world is one of the most popular performance parameters, widely used because it is the answer to the difficulties in calculating the performance measures of banking. The measurement of bank efficiency can be done with Structure Conduct Performance (SCP). In general there are three approaches to the basic concept of financial sector efficiency model that is cost efficiency, standard profit efficiency, and alternative profit efficiency. In this research, the method used is Structure Conduct Performance (SCP). In this method, profit is modeled to be deviated from its efficient efficient frontier due to random noise and inefficiency. Profit in this method is influenced by input and output function, while input and output used in this research are Third Party Fund, Paid-up Capital, placements with Bank Indonesia, placements with other banks, and financing provided.
Keywords: Efficiency; Financial performance; Sharia Bank.